Caracterización agro-socioeconómica del cultivo de jengibre (Zingiber officinale) y su contribución al empleo en el Recinto Cuatro Mangas del Cantón Buena Fe. - Laborde Núñez, Angie Karina (2019)
The present research project is aimed at knowing the agro-productive, social and economic characteristics of ginger production in the Cuatro Mangas Campus, and how economic activity contributes to the generation of employment in the study area; the contextualization of the investigation details the problem of research, diagnosis, prognosis, formulation and systematization of the problem, justification, general and specific objectives; for the development of the theoretical foundation, concepts related to the research theme were collected through the use of primary and secondary sources; the types of descriptive, field and bibliographic research were used; In turn, the inductive, deductive, analytical methods were used. The results obtained indicate that the producers sow half and one hectare of ginger, and their form of sale is classified in marketing per quintal and in boxes of 20kg; 72% of producers sell the product per quintal and 28% in cash; the average cost of production per quintal is 4445.42 and the average cost of production in boxes is $ 5816.39; In the socioeconomic aspect, the producers have mostly primary education, 88% of farmers have their own home and within this percentage a large part have a cement house followed by a small part, they have wooden and mixed constructions, 22% are made up of three people have cement and wood buildings that have been supplied by family members; 64% of producers have as their only income generator the production of ginger while 24% are dedicated to masonry which generates an additional income and 12% are owners of supply stores. Regarding the participation of employment, it was shown that the activities that have the greatest amount of labor in the production of ginger; they are the preparation of the land, planting, harvesting, washing, sorting and packing; in the activities carried out in the field the producer, other relatives, fixed and eventual day laborers participate, the fixed day laborer having a greater presence in the production; In washing, sorting and packaging activities, the female workforce, both familiar and fixed, stands out. Keywords: Socioeconomics, production, cost, job, ginger